1990
DOI: 10.1002/1097-4679(199011)46:6<770::aid-jclp2270460611>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Age differences among psychiatric inpatients on the MCMI

Abstract: A 2 × 2 × 3 MANOVA was applied to MCMI BR scores obtained from 310 newly admitted psychiatric inpatients. The study's purpose was to test the effect of patients' age (age < 36 vs. age > = 36), race (White/Black), and diagnosis (paranoid schizophrenic/nonparanoid schizophrenic/nonpsychotic, nonaffectively disturbed) across MCMI personality and clinical syndrome scales. On the MCMI personality syndrome scales, age, race, and diagnosis were significant. Racial differences were consistent with recently reported re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…This pattern of results is consistent with that produced for hard drug abusers by other cross-sectional studies (Calsyn et al, 2000;McCormick et al, 1998) and with what has been shown by family studies to be the prototypical, possibly genetically mediated, personality phenotype associated with primary substance abuse (Krueger et al, 2002). Also consistent with results of previous studies was the finding that older drug abusers were substantially more mellow than younger ones (Davis and Greenblatt, 1990;Zimmerman and Coryell, 1990).…”
Section: Discussionsupporting
confidence: 91%
“…This pattern of results is consistent with that produced for hard drug abusers by other cross-sectional studies (Calsyn et al, 2000;McCormick et al, 1998) and with what has been shown by family studies to be the prototypical, possibly genetically mediated, personality phenotype associated with primary substance abuse (Krueger et al, 2002). Also consistent with results of previous studies was the finding that older drug abusers were substantially more mellow than younger ones (Davis and Greenblatt, 1990;Zimmerman and Coryell, 1990).…”
Section: Discussionsupporting
confidence: 91%
“…Some researchers suggest differences that emerge may be because of education and socioeconomic status (Greene, 1987; Gynther, 1972). Although some studies have adjusted for age (Davis & Greenblatt, 1990; Davis et al, 1990; Munley, Morris, Murray, & Baines, 2001), no studies to date have adjusted for other potential confounding variables such as education and socioeconomic status. To date, no compelling explanation of these group differences has emerged.…”
mentioning
confidence: 99%
“…A handful of studies have examined the relationship between race and personality pathology. A few studies have found that Black participants scored significantly higher than White participants in cluster A and B PDs (Davis & Greenblatt, 1990; Davis, Greenblatt, & Pochyly, 1990; Hamberger & Hastings, 1992; Munley, Vacha-Haase, Busby, & Paul, 1998). One study found that Black patients scored higher than White patients in cluster A PDs (Choca, Stanley, Peterson, & Van Denburg, 1990).…”
mentioning
confidence: 99%
“…Hyer and Harrison (1986) concluded that the "higher energy" personality types appear to temper with age. Davis and Greenblatt (1990) investigated age differences on the MCMI in a sample of 310 psychiatric inpatients. However, they defined "old" as anyone over 36 years of age and failed to break down the results for specific age groups, thus severely limiting applicability of their results to those over age 55.…”
mentioning
confidence: 99%